Application of Facilitative Learning Model with Photovoice Method in Improving Learning Quality in Youth Education Courses - Sofino, Sofino; Gusti, Ririn; Pradikto, Bayu (JURNAL PAJAR (Pendidikan dan Pengajaran), 2024)
The results of the Learning Evaluation System (SIEPEL V.2) and monitoring of the Quality Control Group (GKM) of the Non-Formal Education Study Program show that the Youth Education (PNF-203) course in semester III of 2022-2023 still experiences difficulties in the implementation and the lowest satisfaction in semester III. This study aims to improve the quality of learning by implementing a facilitative learning model with the photovoice method. Classroom action research was carried out up to 3 cycles by researchers and lecturers in charge of the course collaboratively. The research respondents were 27-semester III-A students in the 2023-2024 academic year. The research results showed that the percentage of learning completion in cycle I was 62.96%, cycle II was 77.78%, and cycle III was 96.30%. The activity observation score for each cycle was 70.4 in cycle I, 81.1 in cycle II, and 85.4 in cycle III. The observation score of lecturer teaching skills was 72.5 in cycle I, 80.25 in cycle II, and 83.5 in cycle III. The facilitative learning model with the photovoice method can improve the quality of learning in youth education courses in the Non-formal Education Study Program.